Tinjauan Literatur: Pengalaman Anak Dirawat Di Ruang Isolasi Rumah Sakit - Tri - Arianingsih; Dessie Wanda (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2021)
Introduction: Isolation is a method of treatment and care for patients with infectious diseases. This has a physical and psychological impact on patients treated in isolation rooms, especially pediatric patients, such as crying, fear, boredom. Objectives: The purpose of this literature review is to reassure the physical and psychological impacts experienced by children during treatment in isolation rooms. Methods: The method used is a literature review. The result total of 9 literature has been analyzed, overall the research conducted showed a negative response (crying, refusing action, fussy, children complaining of boredom, loneliness, sadness, insecurity, feeling threatened, children feeling anxious and fearful). This literature review provides additional evidence about the experiences of children being treated in hospital isolation rooms. Results: The findings from the results of research that have been carried out in this literature review suggest an unpleasant impact of children being treated in hospital isolation rooms. Recommendation: Recommendations from this review literature are giving children distraction techniques to reduce the negative impact experienced by children during the treatment process in hospital isolation rooms. Distraction techniques can be in the form of singing, telling stories, listening to music or watching cartoons.